Surface-Plasmon-Driven Solution-Phase Growth of Germanium Nanostructures on Lithographically Defined Nanogap Antenna Arrays - Hobbs, Richard (My University, 2026)
Low-temperature, spatially selective fabrication of semiconductor nanostructures is essential for next-generation microelectronics, where back-end-of-line (BEOL) thermal budgets limit conventional high-temperature processing. Here, we demonstrate a plasmon-driven, solution-phase route to site-controlled growth of both crystalline and amorphous germanium nanostructures using lithographically defined Au nanoantennas and a diphenylgermane precursor. Resonant excitation at 785 nm of localized surface plasmon resonances (LSPRs) in Au nanogap antenna arrays can generate intense near-field photothermal heating, driving precursor decomposition and Ge nanostructure growth while avoiding global heating of the growth substrate. In this work, we demonstrate plasmon-driven growth of crystalline Ge nanowires at locations determined by lithographically defined Au nanoantennas. Nanowire growth is demonstrated on both bulk ITO/glass substrates and ultrathin 10 nm-thick SiNx membranes to support characterization by transmission electron microscopy. The thermal conductivity of the substrates was found to dictate the optical power threshold required for catalytic nanowire growth. High-resolution TEM confirms the growth of single-crystalline Ge nanowires, while Raman spectroscopy also confirms the growth of Ge nanostructures. This approach may provide a low-thermal budget pathway for production of Ge photodetectors or other nanoelectronic devices directly onto BEOL metallization layers.
PUBLISHED
Keywords: Nanoscience & Materials; Nanochemistry; Nanotechnology; Optical materials